Educational software for the teaching and learning of quadrilaterals generated from a programming language and the dabeja method (2016)
The teaching of math is a process that starts from an early age especially the teaching of geometry through which different representations, constructions, axioms, and theorems among others helps develop the formal thoughts of individuals. This requires not only graphical but demonstrative processes that mentally schemes chords to generate levels of rational thought. Quadrilaterals are part of the components of geometry in the two-dimensional and three-dimensional fields. They possess properties, definitions, classifications, and studies through postulations of parallelism and perpendicularity. Using dynamic strategies and formal processes of knowledge as the Dabeja method to strengthen the teaching of geometry of quadrilaterals through the construction of dynamic courseware, is one of the questions that reveals problems in thought formation. This is an investigation of a parametric quantitative approach with an experimental design of research aimed at the techno de facto and their relationship with the individual development of a formal thinking. An educational software was developed using the Java programming language to construct quadrilaterals, demonstrate their properties and relationships through the Dabeja method.